Stuck on gold: real exchange rate volatility and the rise and fall of the gold standard, 1870-1939 - Natalia Chernyshoff; David S. Jacks; Alan M. Taylor (University of California, Department of Economics, 2005)
Did adoption of the gold standard exacerbate or diminish macroeconomic volatility? Supporters thought so, critics thought not, and theory offers ambiguous messages. A hard exchange-rate regime such as the gold standard might limit monetary shocks if it ties the hands of policy makers. But any decision to forsake exchange-rate flexibility might compromise shock absorption in a world of real shocks and nominal stickiness. A simple model shows how a lack of flexibility can be discerned in the transmission of terms of trade shocks. Evidence on the relationship between real exchange rate volatility and terms of trade volatility from the late nineteenth and early twentieth century exposes a dramatic change. The classical gold standard did absorb shocks, but the interwar gold standard did not, and this historical pattern suggests that the interwar gold standard was a poor regime choice.
Keywords: F33; F41; N10; 330; Goldwährung; Wechselkurs; Terms of Trade; Volatilität; Schock; Theorie; Welt